Moisture Sorption Isotherm and Shelf Life Analysis of Dried Tongkol (Euthynnus affinis) from Aceh - Rita Hayati; Aminah Abdullah; Mohd Khan Ayob; Soewarno T Soekarto (Jurnal Teknologi dan Industri Pangan, 2004)
Tongkol dried fish (Ikan Kayu Tongkol) is lumps of less salted dried fish usually used as popular ingredient for some traditional fish dishes in Aceh as well as in Malaysia. In Japan it is further processed into Katsou-bushi for preparation of special soup. The objective of this research was to find out water relation parameters in the less salted dried fish as related to shelf life, characteristic changes during storage and estimate analysis of it’s expired date. Dried fish samples were equilibrated in 15 levels of RH at 28oC and their equilibrium moisture contents were determined. Moisture sorption isotherm derived from the correlation of equilibrium moisture content data indicated a typical sigmoidal curve implying 3 regions of water adsorption. The water sorption regions accounted for three fractions of bound water as analyzed using three different mathematical models. The first water fraction ranged 0 – 5.95 %, the second 5.95 – 17.52 % and the third fraction ranged 17.52 – 91.12 % dry basis, equivalent to 0 – 5.6 %, 5.6 – 14.9 % and 14.9 – 47.4 % wet basis respectively. Storage simulation experiment in two packaging materials as carried out at 30oC and 90 % RH resulted shelf life of 2749 days (91 months) in the packaging of plastic impregnated allumunium and 1204 days (40 months) in plastic packaging. These very long shelf life was due to the added salt in the produt which increased Mc as high as 46.9 % to cause mold growth. This estimate analysis of shelf life using the mathematical model of Labuza (1984) is one of the appropriate methods to determining expired date of dry food products. Key words : “ Ikan kayu “, skip jack, water sorption isothermi, water fraction, shelflife.